KEBANGKITAN TRANSPORTASI PADA ERA DARING - Tri Susilowati (JURNAL MITRA MANAJEMEN, 2019)
The emergence of online transportation makes it easy for consumers to order without having to wait long to wait, in just a few minutes transportation comes to pick up. This transformation caused chaos in various countries, the organizers of online transportation are required to understand the characteristics of the public transport service industry, by managing the business carefully and innovatively.This is where the role of the Government applies specifically to online transportation. For some countries, special rules need to be applied to online transportation. The government must sit together to formulate how public transport operators and individual businesses are partnering with transportation application companies